2021
DOI: 10.3389/fpubh.2021.743626
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Work Stress on the Associations Between Psychological Job Demands, Social Approval, and Workplace Violence Among Health Care Workers in Sichuan Province of China

Abstract: Objective: The aim of this study was to investigate the prevalence of workplace violence against health care workers, to explore the combined association of work stress, psychological job demands, and social approval with workplace violence and their respective mechanisms among health care workers.Methods: Using data from the Chinese Sixth National Health Service Survey (NHSS) in 2018 conducted among 1,371 health care workers in Sichuan province of China. A self-administered structured questionnaire was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For the positive association between working hours and WPV among FHPs, it may be caused by the work-family conflict for females. For most of the females, they need to take care of their families, and long working hours may result in work-family conflict ( 57 ), which may further result in higher work stress and WPV ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the positive association between working hours and WPV among FHPs, it may be caused by the work-family conflict for females. For most of the females, they need to take care of their families, and long working hours may result in work-family conflict ( 57 ), which may further result in higher work stress and WPV ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a national study, for example, a prevalence of 62% was found among nursing professionals working in oncology 14 . In China 24 and Nigeria 25 , rates in multiprofessional samples were 77% and 88% respectively; and in Bosnia-Herzegovina 26 , it was 90% among primary care physicians and nurses.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the importance of WPV, several studies had been conducted to explore the factors associated with WPV against medical staff, and several associated factors were identified, such as social-demographic (12,13), psychological and physical health (9,(14)(15)(16)(17)(18), and work-related variables (19)(20)(21)(22). For work-related variables, most of these studies focused on the association between work stress, work burnout, social support, work environment, and WPV (19)(20)(21)(22). The work for medical staff was characterized by long working hours, frequent night duty, and a high workload (23,24).…”
Section: Discussionmentioning
confidence: 99%